Antidumping Investigations on Shrimp Exports from India to US - A Case Study - Gopal, Nikita; V., Geethalakshmi; G.R., Unnithan (Fishery Technology, 2025)
The anti-dumping investigation against India and five other major shrimp exporting countries by the US was initiated in December 2003. This paper examines the impact on the quantity and value of shrimp imports from these countries in general and India in particular, during the period of investigation and after. It was observed that there has been a negative impact on Indian shrimp exporters and the number of exporters has decreased considerably. The effect on the price in the US market has been negligible with the unit value of imports actually falling. Only a short-term rise in price index was observed during the initial phase of the investigation period as well as the period when the affirmative decision was announced.